2007
DOI: 10.1111/j.1365-294x.2007.03244.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiation and speciation of pelagic organisms during periods of global warming: the case of the common minke whale, Balaenoptera acutorostrata

Abstract: How do populations of highly mobile species inhabiting open environments become reproductively isolated and evolve into new species? We test the hypothesis that elevated ocean-surface temperatures can facilitate allopatry among pelagic populations and thus promote speciation. Oceanographic modelling has shown that increasing surface temperatures cause localization and reduction of upwelling, leading to fragmentation of feeding areas critical to pelagic species. We test our hypothesis by genetic analyses of pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
107
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(120 citation statements)
references
References 47 publications
11
107
2
Order By: Relevance
“…Periods of global cooling with associated high upwelling intensities were alternated by extended periods of global warming (Zachos et al, 2001) during which upwelling areas (Schmittner, 2005;Fedorov et al, 2013;Ravelo et al, 2004) and related productivity (Diester-Haass et al, 2002;Marlow et al, 2000;Piela et al, 2012;Suto et al, 2012) were reduced. Hence, hypothetically, global warming may have resulted in fragmentation of the habitat of filter feeders, leading to different subpopulations eventually residing in smaller isolated regions, which may have facilitated speciation as suggested for the common minke whale (Balaenoptera acutorostrata) and Antarctic minke whale (B. bonaerensis) (Pastene et al, 2007). Our divergence estimates coincide broadly with several periods of global warming making such a mechanism conceivable for mobulids.…”
Section: Mechanisms and Drivers Of Mobulid Speciationsupporting
confidence: 65%
See 1 more Smart Citation
“…Periods of global cooling with associated high upwelling intensities were alternated by extended periods of global warming (Zachos et al, 2001) during which upwelling areas (Schmittner, 2005;Fedorov et al, 2013;Ravelo et al, 2004) and related productivity (Diester-Haass et al, 2002;Marlow et al, 2000;Piela et al, 2012;Suto et al, 2012) were reduced. Hence, hypothetically, global warming may have resulted in fragmentation of the habitat of filter feeders, leading to different subpopulations eventually residing in smaller isolated regions, which may have facilitated speciation as suggested for the common minke whale (Balaenoptera acutorostrata) and Antarctic minke whale (B. bonaerensis) (Pastene et al, 2007). Our divergence estimates coincide broadly with several periods of global warming making such a mechanism conceivable for mobulids.…”
Section: Mechanisms and Drivers Of Mobulid Speciationsupporting
confidence: 65%
“…The upwelling hypothesis has also been proposed for the mysticeti whales, whose early evolution in Southern Oceans coincides with the initiation of the Antarctic Circumpolar Current, and associated high upwellingrelated productivity in this region during the Oligocene (Fordyce, 1980). Pastene et al (2007) suggested that periodic decreases in upwelling intensity through global warming could have facilitated allopatric speciation among pelagic populations of filter feeders. Upwelling has not been a stable phenomenon, but has waxed and waned following changes in the world's climate throughout the ages.…”
Section: Mechanisms and Drivers Of Mobulid Speciationmentioning
confidence: 88%
“…This was confirmed by histopathology, which showed alveolar flooding consistent with aspiration or lung edema, all other tissue structure being within normal limits. Mitochondrial DNA control region sequencing found the male calf to be related to the north Atlantic stock of common minke whale [16]. Two other calf mortalities of unknown cause were investigated.…”
Section: Strandingsmentioning
confidence: 99%
“…Population differentiation in cetaceans, for example, is frequently driven by opposite reproductive seasonality in northern and southern hemispheres (Hoelzel 1998, Pastene et al 2007). Data on seasonality and location of spawning by D. gigas are sparse but tantalizing.…”
Section: North-south Genetic Breakmentioning
confidence: 99%